PEMODELAN HASIL REKAYASA KEBUTUHAN PERANGKAT LUNAK SISTEM JURNAL ELEKTRONIK TERINTEGRASI "IDEOGRAM" - Ridwan Dwi Irawan; Muh Adha; Muhammad Paliya Sadana; Zitnaa Dhiaaul Kusnaa Washilatul Arba’ah; Ema Utami (JURNAL INFORMATIKA DAN KOMPUTER, 2023)
E-Journal or Electronic Journal can be interpreted as online storage of information and communication. The characteristics of the E-Journal are that it utilizes electronic technology where publishers, writers, and readers can communicate with each other and use ICT, or written work data is stored so that it can be accessed anywhere and anytime when needed. One of the efforts to increase the effectiveness and efficiency of the scientific publication process requires using various ICTs. Design can use the electronic journal information system to solve problems in compiling a journal integration system based on software requirements analysis. In addition, the system development method used is a waterfall. The design uses UML, ERD, Wireframe, and database implementation using DBMS. The research results are realized in the form of a conceptual design of the system so that it can accommodate the needs to make the system. The development also can choose journals that are following their fields so that they can estimate open access journals based on the estimated submission time.